Reasons, Views and Practices of Nonnative Parents towards Raising Bilingual Children - Karagöz, Sıdıka; Erdemir, Nihan (My University, 2022)
With the rise of English as a global language, bilingualism has drawn considerable interest among non-native English speakers. For this reason, this study aims to investigate the reasons, views, and practices of English as a foreign language (EFL) teachers as parents about their raising a bilingual child. The study adopted an interview technique among qualitative research designs. The data of the pilot and main studies were collected through purposive sampling according to predetermined criteria from nine parents who are nonnative English speakers, raise a bilingual child, and work as EFL teachers at state schools in Turkey. Participants were interviewed with semi-structured interview questions. All responses were analyzed by content analysis in NVivo 12, and interrater reliability was calculated. The findings showed that parents had a higher number of academic- and life-related reasons for raising bilingual children such as living abroad, traveling in the world, studying at bilingual schools, and having developed cognitive skills. Their views towards advantages were similarly rooted in academic and life themes. However, the disadvantages were rather related to child-, society- and family themes and mainly included having language delays, being prejudiced by the society, and being discouraged by family members. Regarding the bilingual practices of parents, the study highlighted that parents were mostly unaware of scholarly approaches to bilingual parenting methods and intuitively acted in their own manner. Therefore, families are suggested to initiate bilingual upbringing after having sufficient knowledge of academic methods and practices in order to consider the factors affecting a child’s emotional and social development as well as cognitive, and also they might inform their acquaintances about possible delays and confusion in advance in order to lessen anxiety and their fear of communication with the child.
Keywords: EFL teachers; Qualitative research; Bilingualism; Nonnative parents